Interaction between nitrate and trichloroethene bioreduction in mixed anaerobic cultures - Yang, Dong-Mei; Min, Fen-Li; Li, Ying; Ling, Jia-Lu; Zhong, Hui-Xian; Xia, Yu-Chun; Feng, Ying; Zhao, Li-Ya; Li, Zhao-Hua; Wen, Li-Lian (Frontiers in Microbiology, 2025)
Bioremediation of trichloroethene (TCE)-contaminated sites often leads to groundwater acidification, while nitrate-polluted sites tend to generate alkalization. TCE and nitrate often coexist at contaminated sites; however, the pH variation caused by nitrate self-alkalization and TCE self-acidification and how these processes affect nitrate reduction and reductive dichlorination, have not been studied. This study investigated the interaction between nitrate and TCE, two common groundwater co-contaminants, during bioreduction in serum bottles containing synthetic mineral salt media and microbial consortia. Our results showed that TCE concentrations up to 0.3 mM stimulated nitrate reduction, while the effect of nitrate on TCE reductive dechlorination was more complex. Nitrate primarily inhibited the reduction of TCE to dichloroethene (DCE) but enhanced the reduction of vinyl chloride (VC) to ethene. Mechanistic analysis suggested that this inhibition was due to the thermodynamic favorability of nitrate reduction over TCE reduction, while the promotion of VC reduction was linked to pH stabilization via self-alkalization. As the initial nitrate concentration increased from 0 to 3 mM, the relative abundance of putatively denitrifying genera, such as Petrimonas and Trichlorobacter, increased. However, the abundance of fermentative Clostridium sharply declined from 31.11 to 1.51%, indicating strong nitrate inhibition. Additionally, the relative abundance of Dehalococcoides, a genus capable of reducing TCE to ethene, slightly increased from 23.91 to 24.26% at nitrate concentrations up to 0.3 mM but decreased to 18.65% as the nitrate concentration increased to 3 mM, suggesting that Dehalococcoides exhibits a degree of tolerance to high nitrate concentrations under specific conditions. Overall, our findings highlight the potential for simultaneous reduction of TCE and nitrate, even at elevated concentrations, facilitated by self-regulating pH control in anaerobic mixed dechlorinating consortia. This study provides novel insights into bioremediation strategies for addressing co-contaminated sites.